Sediment cores from shallow lakes preserve reliable, informative paleoenvironmental archives despite hurricane-force winds. (January 2016) - Kenney, William F.; Brenner, Mark; Arnold, T. Elliott; Curtis, Jason H.; Schelske, Claire L.
Abstract: Comparison of sediment cores collected in 1999 and 2013 from shallow Lake Harris, Florida, USA showed that the sediment maintained stratigraphic integrity despite multiple hurricanes passing through the area in 2004. Sediments less than 50 years old displayed small losses of organic matter (OM), total phosphorus (TP) and heat-extractable (HE-P) through time that are unrelated to hurricane impacts. Nevertheless, sediment that accumulated between the two core collection dates contained 4-fold more TP than was lost from the sediment over the 14-year period, indicating that sediments in Lake Harris are a net sink for water-column TP. Persistent, elevated 137 Cs activity in sediments deposited since the mid-1960s indicates protracted cesium input to the lake from this subtropical watershed. There is also evidence for downward transport of 137 Cs in the sediment profile between core collection dates. Prolonged export of 137 Cs from the watershed and downward mobility of the radionuclide in the sediment profile diminish the utility of 137 Cs as a dating tool in Lake Harris.